2019
DOI: 10.1177/0004867419864433
|View full text |Cite
|
Sign up to set email alerts
|

Are claims of non-inferiority of Internet and computer-based cognitive-behavioural therapy compared with in-person cognitive-behavioural therapy for adults with anxiety disorders supported by the evidence from head-to-head randomised controlled trials? A systematic review

Abstract: Objective: This review examines the evidence from head-to-head randomised controlled trials addressing whether the efficacy of cognitive-behavioural therapy for anxiety disorders, obsessive-compulsive disorder and post-traumatic stress disorders in adults delivered by computer or online (computer- and Internet-delivered cognitive-behavioural therapy) is not inferior to in-person cognitive-behavioural therapy for reducing levels of symptoms and producing clinically significant gains at post-treatment and at fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…9,10 In contrast, a systematic review found that there was no substantive evidence iCBT was equally beneficial to in-person CBT for anxiety disorders. 11 There is good evidence for the efficacy of online-delivered interpersonal psychotherapy, 12 acceptance and commitment therapy 13 and psychodynamic approaches. 14 Although these approaches can be self-guided, therapist support makes a substantial difference in terms of adherence, completion and efficacy.…”
Section: Effectiveness Of Internet-delivered Interventions (Self-guided Versus Clinician-guided)mentioning
confidence: 99%
“…9,10 In contrast, a systematic review found that there was no substantive evidence iCBT was equally beneficial to in-person CBT for anxiety disorders. 11 There is good evidence for the efficacy of online-delivered interpersonal psychotherapy, 12 acceptance and commitment therapy 13 and psychodynamic approaches. 14 Although these approaches can be self-guided, therapist support makes a substantial difference in terms of adherence, completion and efficacy.…”
Section: Effectiveness Of Internet-delivered Interventions (Self-guided Versus Clinician-guided)mentioning
confidence: 99%
“…Nevertheless, individuals with serious mental illnesses can struggle to connect cognitively and emotionally during telehealth sessions with their counsellor [ 68 ]. Another systematic review of 14 RCTs of iCBT found no substantive evidence that iCBT was equally beneficial for patients with anxiety disorders as in-person services [ 69 •], starkly contrasting previously described research [ 30 •, 31 ]. It is also important to consider that more than 40% of the most rural USA counties do not have the necessary broadband infrastructure to support video based telehealth [ 46 ].…”
Section: Evidence On the Use Of Telepsychiatry For Mental Healthmentioning
confidence: 85%
“…However, we were unable to identify further studies within the review's inclusion criteria that compared Interapy to active comparison conditions. Although there is a growing body of evidence showing the efficacy of online CBT‐informed interventions for various mental health conditions compared to waitlist conditions (Adelman et al., 2014), there remain significant methodological limitations in the literature for its efficacy in comparison to in‐person CBT (O'Kearney et al., 2019). Despite this, online delivery offers many advantages, including better accessibility and reduced costs (Andrews et al., 2018).…”
Section: Discussionmentioning
confidence: 99%